A Beam Network Model Approach to Strength Optimization of Disordered Fibrous Materials. Issue 9 (4th November 2019) - Hosseini, Seyyed Ahmad; Moretti, Paolo; Zaiser, Michael
Abstract : A beam network model is used to study the nucleation and propagation of cracks in uniaxially loaded materials consisting of randomly cross‐linked fibers with statistically distributed failure thresholds. The failure behavior of such materials is investigated and, for different degrees of disorder, the fraction of cross links required to achieve an optimal strength‐to‐weight ratio is determined. In the absence of disorder, this problem has a trivial analytical solution (no cross links), which however turns out the worst possible arrangement for strongly disordered materials and/or for large system sizes. Abstract : Networks of breakable beams are used to model fracture in fibrous materials of increasing heterogeneity. In ideal homogeneous systems, the optimal strength‐to‐weight ratio is obtained in the absence of cross‐linking fibers, which do not contribute to the overall system toughness. Upon increasing the fiber heterogeneity, however, cross‐links ensure load redistribution and are found to effectively strengthen the fibrous system.